The Old City of Al Zubair. The emergence and physical reality (1571-1882 Iraq) - Alqatrani, Firas Sami Abdulaziz (Bulletin of Geography. Socio-economic Series, 2015)
The natural advantages of the site of the city of Al Zubair contributed to its becoming a stable settlement for the tribes migrating from Najd and Hejaz during the last four centuries. These features gave the city a fundamental stability and constant growth, turning it, later, into one of the main cities in the region and an important commercial centre. This research study aims to examine the historical dimensions of Al Zubair’s emergence, as well as the physical housing reality within the boundaries of the walled city (which represents the first phase of the city’s development), and to identify the role of people adapting the local conditions of the place in ways that made it a suitable environment for human habitation. The morphological method has been used in this study of the physical reality of the city. This sequential historical method grants geography an important third dimension: time. Al Zubair is, in terms of its architecture, a history written in the form of buildings, streets, and various other facilities; it is an historic compound that cannot be comprehended without an understanding of and insight into its historical development.